Effect of playing tactics on achieving score-box possessions in a random series of team possessions from Norwegian professional soccer matches - Tenga, A.; Holme, I.; Ronglan, L. T.; Bahr, R. (Journal of Sports Sciences, 2010)
Methods of analysis that include an assessment of opponent interactions are thought to provide a more valid means of team match performance. The purpose of this study was to examine the effect of playing tactics on achieving score-box possession by assessing opponent interactions in Norwegian elite soccer matches. We analysed a random series of 1703 team possessions from 163 of 182 (90%) matches played in the professional men's league during the 2004 season. Multidimensional qualitative data obtained from ten ordered categorical variables were used. Offensive tactics were more effective in producing score-box possessions when playing against an imbalanced defence (28.5%) than against a balanced defence (6.5%) (P < 0.001). Multiple logistic regression found that, for the main variable "team possession type", counterattacks were more effective than elaborate attacks when playing against an imbalanced defence (odds ratio: 2.69; 95% confidence interval: 1.64 to 4.43) but not against a balanced defence (odds ratio: 1.14; 95% confidence interval: 0.47 to 2.76). Assessment of opponent interactions is critical to evaluate the effectiveness of offensive playing tactics on producing score-box possessions, and improves the validity of team match-performance analysis in soccer.